Jawabanmu

2014-03-21T08:25:57+07:00
F(x) = 2(x+1)3 - 6(x+1)
     = (2x +2)3 - (6x - 6)
     = 6x + 6 - 6x - 6
     = 0

f(x) = g(x) -----> kita misalkan nilainya adlah 2

f(x) = 3.2 -6
       = 0

g(x) = 2.2 + a
     0 = 4 + (-4)

yg no 2 aq bgung...

2 3 2
2014-03-21T08:31:26+07:00
1. f(x +1) = 2(x + 1)^3 - 6(x + 1)
              = 2(x^3 + 3x^2 + 3x + 1) - 6x - 6
              = 6x^3 + 6x^2 + 6x +2 - 6x - 6
              = 2x^3 + 6x^2 - 4
2. (fog)(x) = (gof)(x)
     f(g(x)) = g(f(x))
     f(2x+a) = g(3x-6)
     3(2x+a) - 6 = 2(3x-6) + a
     6x + 3a - 6 = 6x - 12 + a
     2a = - 6
     a = - 3